Hypokalemia Periodic Paralysis in Subtle Thyrotoxicosis with Renal Insufficiency - Indah Sagitaisna Putri; Dadang Herdiana; Pipik Ripa’I; Miko Galastri (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Hypokalemia is one of the frequently observed electrolyte imbalances in clinical practice. The clinical manifestations range from asymptomatic to significant manifestation, such as paralysis. Here we report a case of 31-years-old female admitted to our emergency department with chief complaint of acute onset of paralysis in lower extremities. Vital signs showed slight tachycardia. The physical examinations were all normal. Motoric examination showed paraparesis in lower extremities with normal sensory function. Upon admission, laboratory tests showed severe hypokalemia (1.5 mmol/L) with renal insufficiency. The patient got hypokalemia corrected with both potassium oral supplementation and potassium infusion. Thyroid function tests showed hyperthyroidism and the diagnosis of thyrotoxic periodic paralytic (TPP) was made. This case report highlights the importance of early diagnosis and prompt treatment of hypocalemia in TPP patient.